Fine coal beneficiation: comparison study of the separation efficiency of a dense medium cyclone and flat-bottom cyclone - Lumbela, Naledi (Department of Chemical Engineering, 2025)
Near-gravity material (NGM) is the fraction of coal particles with a relative density within a range of ± 0.1 of the relative density of the separating medium during coal washing. High levels of NGM in coal impede classifier separation efficiency because NGM particles have low settling rates, which hinder free particle movement during classification. Low-grade coal has a high ash and near-gravity material content, making it economically unviable to beneficiate. As near-gravity material (NGM) concentration increases, the efficient beneficiation of clean coal from middlings and rejects becomes challenging, hindering the reduction of ash-bearing impurities. High NGM levels obscure the separation boundaries between middlings and reject coal, complicating product extraction and handling. This reduces the efficiency of coal beneficiation processes. Therefore, this study is undertaken to investigate which classifier between a dense medium cyclone and a flat-bottom cyclone can optimally beneficiate the NGM-laden coal. A conventional hydrocyclone was modified into a flat-bottom cyclone with an extended cylindrical section and wide cone angle to promote the formation of an autogenous separating medium. This cyclone is sometimes called a water-only cyclone (WoC) in coal washing. The flat-bottom cyclone (FBC) uses no media except water to create an autogenous medium that promotes separation by density. In contrast, the dense medium cyclone (DMC) drives separation by density by using an external heavy media to create a sharp density difference between the coal, gangue particles and the heavy media. Each classifier experiment investigated the impact of three parameters on cyclone separation efficiency when beneficiating low-grade coal with high NGM and ash-bearing impurities content. The flat-bottom cyclone parameters included vortex finder diameter, spigot diameter, and solids concentration, each tested at three levels. For the dense medium cyclone, the parameters were vortex finder diameter, spigot diameter, and medium density, also varied at three levels. The central composite rotatable design (CCRD) was employed to model and numerically optimise the operating variables of the classifiers to minimise the ash content in the final product coal. Classifier separation performance was analysed through partition curves, density cut-point, sharpness of separation, organic efficiency, and particle misplacement. The results indicate that for the dense medium cyclone, the vortex finder diameter significantly influences the ash content of the recovered coal yield. In contrast, for the flat-bottom cyclone (FBC), the spigot diameter is the primary factor affecting ash content. Regression models developed for ash content showed strong agreement with experimental data, achieving R² values of 0.78 for the flat-bottom cyclone and 0.80 for the dense medium cyclone. Under optimised conditions, the dense medium cyclone demonstrated sharper separation, lower particle misplacement, and better ash reduction. Conversely, the flat-bottom cyclone showed lower ash removal efficiency, higher clean coal particle misplacement, and poor separation performance.